Investigation of the Effectiveness of Intensive Reading (IR) with Authentic Materials on Students’ Reading Ability toward English Proficiency Test for Students of STKIP PGRI Bangkalan - Ridwan, Arfiyan (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2016)
The current research investigates the effect of online intensive reading (IR) on students’ reading ability on English proficiency test. Besides, students’ perceptions on the use of online intensive reading were also studied. A number of credible journals indexed in SCOPUS are used to support online intensive reading. Eighty students are involved in this study into two groups in which 40 students to be assigned as experimental group and 40 students to be assigned as control group. Students’ perceptions on online intensive reading were investigated after questionnaires had been spread. In addition, independent sample t test was used to find out the score difference between the experimental group and control group. A significant difference was found in the gained score difference between the experimental group with online intensive reading and control group with non-online intensive reading in which p value .000< significance .05. in addition to the findings, It was found that students attained overall good perceptions toward reading journal articles related to suitability, reading pace, and motivation The result of this research is on educational implication that teaching reading with online intensive reading is found effective.